Fate of nonylphenol ethoxylate (NPEO) and its inhibitory impact on the biodegradation of acetate under aerobic conditions - Ekdal, Alpaslan (Environmental technology, 2014)
This study evaluated the kinetics of nonylphenol ethoxylate (NPEO) and acetate biodegradation at a moderate sludge age by acclimated culture under aerobic conditions. A laboratory-scale sequencing batch reactor was set and fed only with acetate mixture. The system was operated at steady state with a sludge age of 8 days. Following this stage, a mixture of NPEO and acetate was fed to the mixed culture in order to assess the biodegradation kinetics of NPEO and its impact on acetate utilization. A mechanistic model was developed involving model components and kinetic parameters for both substrates. The model was calibrated with parameters such as oxygen uptake rate and polyhydroxyalkanoates. Biodegradation characteristics and kinetics of acetate and NPEO were estimated by using the model results. Evaluation of calibrated model indicated that exposure of NPEO to non-acclimated sludge caused significant inhibitory impact on the utilization and storage of acetate. However, acclimation ofbiomass greatly suppressed inhibitory effects of NPEO on growth process involved in the degradation of acetate